Pharmacogenovigilance: A Potential Tool in Pharmacovigilance - Mainul, Haque; Nordin, Simbak; Adamu, Yau (2014)
Pharmacogenovigilance is a program which can be developed by integrating pharmacogenomics into a pharmacovigilance studies. The fact that genes play a vital role in variability in response to medicines makes pharmacogenomic of adverse drug reactions (ADRs) very essential program. Genetic variations have significantly affected the drug action in many patients, and a time predisposes patient to uncommon ADRs that are not seen in other patients. Pharmacogenetics provides greener path to individualized use of medicines, drug safety and efficacy studies due to genetic polymorphism. In order to explore these potential benefits, integration of pharmacogenovigilance in to clinical practice and public health system has become necessary. It is imperative for every medical practitioner to consider genetic factors in order to prescribe the best medication to his patients. Literature search using terms genetic biomarkers, application of pharmacogenetics and pharmacogenomics, and influence of pharmacogenetics on pharmacovigilance was done using PubMed, PhamaKG, US FDA and WHO websites. Several challenges facing drug safety and pharmacovigilance were highlighted and proposed pharmacogenomics approaches in solving them. The purpose of this article is to justify pharmacogenovigilance as an essential tool for drug safety and efficacy while providing the most feasible way for its successful integration in to the cycle of patients care. In conclusion, considerable progresses have been recorded on the potentials of pharmacogenovigilance in drug safety and efficacy study during post-marketing surveillance, and based on the provided evidences, the right time for pharmacogenovigilance is now.